THE INDONESIA-TURKEY FOREIGN TRADE - Selminaz Adıgüzel; Eko Fajar (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
The aim of this research is to investigate the effects of foreign trade of Indonesia and Turkey on economic growth between 2012 and 2023. The Data came from both countries’ official institution like Statistic Agency, Ministry of Trade, Ministry of Finance. The Period from 2012 until 2023. As research methods, Autoregressive Distributed Lag Bounds approach for cointegration and Toda and Yamamoto causality test were used. The effect of foreign trade on economic growth has been the subject of scientific research. To estimate the impact of foreign trade on economic growth, it was tested whether the time series were stationary or not. For time series analysis to be realistic, the data must be stationary. Time series stationarity structure was determined by the Augmented Dickey-Fuller (ADF) test. Long-term relationships of the variables were analyzed by cointegration test. The causality relationship between variables is given with the Granger Causality Test. This research aims to determine the effect of exports and imports on economic growth.